Optimizing the Performance of the Kamsel Unit Through Dikmas Lantas in Preventing Traffic Violations by Students in the Jurisdiction of the Tegal Police - Kurniawan, Desta Candra (Advances in Police Science Research Journal, 2024)
The increasing number of traffic violations committed by students in the jurisdiction of Tegal Resort Police motivated the author to write a final project related to the optimization of the performance of the Kamsel Unit of the Tegal Resort Police in implementing Dikmas Lantas. This writing aims to describe the management of the Kamsel Unit of the Tegal Police Station in implementing Dikmas Lantas to prevent traffic violations by students and the organizational resources of the Kamsel Unit of the Tegal Police Station in supporting the implementation of Dikmas Lantas to students. A qualitative approach with data collection techniques through observation, interviews, and document review is used in the final assignment. The author uses management theory, SWOT analysis theory, hierarchical needs theory, the concept of prevention, the concept of traffic violations, the concept of optimization, the concept of administration of facilities and infrastructure, and the concept of Dikmas Lantas as an analytical knife in describing the existing problems. The implementation of the Dikmas Lantas conducted by the Kamsel Unit of the Tegal Traffic Police still have some obstacles in the planning stage to supervision, as well as the lack of organizational resources owned by the Kamsel Unit of the Tegal Traffic Police in supporting the implementation of Dikmas Lantas. These problems include the absence of schedule and target planning, uneven division of tasks, not reaching all areas, lack of personnel, and lack of creativity and materials that are not by the objectives of the implementation of Dikmas Lantas. The Kamsel Unit of the Tegal Police Station must be aware of the shortcomings in the implementation of Dikmas Lantas to students, and carry out the steps that have been given by the author.This aims to optimize the implementation of Dikmas Lantas, so that the number of traffic violations committed by students decreases.